Farmer’s Perception of Fruit Fly Bactrocera spp. in Mandarin Orange and their Management in Sankhuwasabha District of Nepal - Rai, A; Sah, L P; Adhikari, K; Shrestha, K (Journal of the Plant Protection Society, 2022)
The study was conducted from October to December, 2020 to evaluate farmers' understanding of loss incurred by Bactrocera spp. on mandarin orange and practices adopted by farmers for their management. Eighty households of mandarin orange growers and 15 agro-vets were purposively selected and information was collected using a semi structured questionnaire. The findings indicated severe infestation of fruit fly in mandarin with 53% of the farmers having low (>15%), 36% having medium (15-30%) and 11% having high (>30%) level of fruit damage in their orchards. The survey identified several management practices like collection and destruction of fallen fruits, pruning, use of traps and chemical pesticides in controlling fruit fly. About two-third (61.25%) of the respondents used chemicals and 15% of the farmers collected and destroyed affected fallen fruits. Some farmers also practiced pruning in the study area for the control of fruit fly. The use of traps was a rarity and its use was limited to only 10% of the total respondents. Since farmers were not much aware of the impact, life cycle and different species of fruit fly, lacked adequate training, support, and supervision, effective management of fruit fly was not possible and resulted in a much greater damage in mandarin fruit.